2022
DOI: 10.2147/jir.s353467
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Brain Injury: The Potential Role of Ferroptosis

Abstract: The COVID-19 pandemic has caused devastating loss of life and a healthcare crisis worldwide. SARS-CoV-2 is the causative pathogen of COVID-19 and is transmitted mainly through the respiratory tract, where the virus infects host cells by binding to the ACE2 receptor. SARS-CoV-2 infection is associated with acute pneumonia, but neuropsychiatric symptoms and different brain injuries are also present. The possible routes by which SARS-CoV-2 invades the brain are unclear, as are the mechanisms underlying brain inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 174 publications
(238 reference statements)
1
21
0
4
Order By: Relevance
“…Previous studies have also reported that ferroptosis may also play a potential role in the development of COVID-19-related brain injuries as Fe is one of the most abundant metals found in the brain and is needed for normal physiological processes of the brain. The brain is also sensitive to oxidative stress generated by ROS and lipid peroxidation due to its high level of PUFAs as the cell membranes of the neurons contain high amounts of PUFAs, thus being susceptible to ROS-mediated oxidation caused by a cytokine storm, a key feature of SARS-CoV-2 infection in COVID-19 [237,238]. Ferroptosis may also occur due to the dysregulation of Fe homeostasis in COVID-19 patients.…”
Section: Ferroptosis In Viral Infectionmentioning
confidence: 99%
“…Previous studies have also reported that ferroptosis may also play a potential role in the development of COVID-19-related brain injuries as Fe is one of the most abundant metals found in the brain and is needed for normal physiological processes of the brain. The brain is also sensitive to oxidative stress generated by ROS and lipid peroxidation due to its high level of PUFAs as the cell membranes of the neurons contain high amounts of PUFAs, thus being susceptible to ROS-mediated oxidation caused by a cytokine storm, a key feature of SARS-CoV-2 infection in COVID-19 [237,238]. Ferroptosis may also occur due to the dysregulation of Fe homeostasis in COVID-19 patients.…”
Section: Ferroptosis In Viral Infectionmentioning
confidence: 99%
“…ROS, reactive nitrogen species, and reactive sulfur species ( 116 , 120 , 121 ) produced during pathological conditions can cause oxidative damage and ischemia-reperfusion injury to different organs, such as the lungs, liver, kidney, heart, intestine, and brain ( 122 124 ). To a great extent, ferroptosis is associated with hyperinsulinemia, hypercoagulable state, hemorrhagic stroke injury, shock, and MODS ( 123 , 125 , 126 ).…”
Section: Regulated Necrosis In Covid-19: a Double-edged Sword?mentioning
confidence: 99%
“…Em relação ao sistema nervoso central, o coronavírus ataca o cérebro através de três caminhos diferentes, sendo eles: líquido cefalorraquidiano, nervos periféricos e vasos sanguíneos, se houver rompimento da barreira hematoencefálica. Tal lesão na barreira pode ocorrer pelo excesso de citocinas e, consequentemente, pelo recrutamento de células inflamatórias para o local (Zhang et al, 2022). Foram descritos inúmeros sintomas neuropsiquiátricos e, segundo Zhang et al (2022), eles são decorrentes de lesões diretas nas células cerebrais, causadas pela invasão do SARS-CoV-2 nos receptores ECA2 e de microderrames ou micro-hemorragias no tecido nervoso que, por sua vez, surgem devido à liberação de trombina pelas células endoteliais do cérebro ao sofrerem agressões.…”
Section: • Efeitos Sistêmicos Do Coronavírusunclassified
“…Tal lesão na barreira pode ocorrer pelo excesso de citocinas e, consequentemente, pelo recrutamento de células inflamatórias para o local (Zhang et al, 2022). Foram descritos inúmeros sintomas neuropsiquiátricos e, segundo Zhang et al (2022), eles são decorrentes de lesões diretas nas células cerebrais, causadas pela invasão do SARS-CoV-2 nos receptores ECA2 e de microderrames ou micro-hemorragias no tecido nervoso que, por sua vez, surgem devido à liberação de trombina pelas células endoteliais do cérebro ao sofrerem agressões. A trombina pertence a uma das etapas fundamentais da coagulação e posterior formação de trombos.…”
Section: • Efeitos Sistêmicos Do Coronavírusunclassified
See 1 more Smart Citation